2021
DOI: 10.3389/fpls.2021.694179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Morphological Characteristics, Mineral Nutrition, Nitrogen Metabolism, and Energy Status in Alfalfa Under High-Nitrate Stress

Abstract: Melatonin is an indoleamine small molecular substance that has been shown to play an important role in the growth, development, and stress response of plants. The effects of melatonin on the morphological characteristics, mineral nutrition, nitrogen metabolism, and energy status in alfalfa (Medicago sativa L.) under high-nitrate stress were studied. The alfalfa plants were treated with water (CK), 200 mmol L−1 nitrates (HN), or 200 mmol L−1 nitrates + 0.1 mmol L−1 melatonin (HN+MT), and then were sampled for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
(102 reference statements)
1
11
0
Order By: Relevance
“…Exogenous melatonin with KNO 3 promotes the antioxidant enzymes and enhances the nitrogen metabolism activities of maize under waterlogging stress conditions. The glutathione synthase (GS), nitrate reductase (NR), glutamate synthetase (GOGAT), and glutamate dehydrogenase (GDH) enzymes play important roles in nitrogen metabolism [ 58 ]. We found that under WL stress, the GS and NR were reduced compared with NWL and WLM.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous melatonin with KNO 3 promotes the antioxidant enzymes and enhances the nitrogen metabolism activities of maize under waterlogging stress conditions. The glutathione synthase (GS), nitrate reductase (NR), glutamate synthetase (GOGAT), and glutamate dehydrogenase (GDH) enzymes play important roles in nitrogen metabolism [ 58 ]. We found that under WL stress, the GS and NR were reduced compared with NWL and WLM.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, melatonin increased nitrogen-excess tolerance through the up-regulation of NR, GS, GOGAT, and GDH enzymes. Furthermore, it reduced the total nitrogen levels (nitrate and ammonium content) and increased the biomass, length, width of leaves, and energy levels (P and ATP) and decreased the Na, K, and Ca mineral contents [ 48 ]. Similar results were obtained in soybean plants treated with melatonin in nitrogen-excess [ 49 ].…”
Section: Role Of Melatonin In Nitrogen Metabolismmentioning
confidence: 99%
“…It also improved the contents of amino acid, protein, proline, and ureides, whilst up-regulating NR, NiR, NRT, GS, GOGAT, and GDH gene expression, consequently improving the growth and total biomass of soybean plants [ 56 ]. The authors suggested that melatonin regulated the assimilation, metabolism and transport of nitrogen, thereby maintaining the carbon/nitrogen balance [ 48 , 50 , 58 , 59 ].…”
Section: Role Of Melatonin In Nitrogen Metabolismmentioning
confidence: 99%
“…Melatonin (MT) is an important hormone synthesized naturally in both plants and animals. Many recent studies have documented that MT is critical in several metabolic processes, including ROS scavenging systems ( Siddiqui et al, 2020a , b ), secondary metabolism ( Farouk and Al-Amri, 2019 ; Jahan et al, 2020 ), and modulation of nitrogen metabolism ( Qiao et al, 2019 ; Chen et al, 2021 ; Meng et al, 2021 ; Kaya et al, 2022 ). Therefore, MT plays a significant role in plants to cope with biotic and abiotic stresses ( Arnao and Hernández-Ruiz, 2015 , 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%